Pengaruh Kualitas Pelayanan, Citra LPD dan Kepercayaan Nasabah Terhadap Kepuasan Nasabah Kredit Pada LPD Desa Pakraman Yeh Bakung di Tabanan - Adhi Mahaputra, I Gusti Agung Made Arri; Susanti, Putu Herny (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Perceived satisfaction shows the company’s success in meeting customer expectations. Conducting this research is expected to determine the effect of service quality, image, and customer trust on credit customer satisfaction at LPD Desa Pakraman Yeh Bakung in Tabanan. The sample used in this study amounted to 91 people who were selected by accidental sampling method. The data obtained were analyzed using multiple linear regression. From the research results, it was found that, service quality, LPD image and customer trust were able to influence credit customer satisfaction at LPD Desa Pakraman Yeh Bakung in Tabanan either partially or simultaneously positively and significantly. To the LPD, management should maintain and improve customer satisfaction by observing the factors of service quality, image and trust.